Numerical study of hydro-environmental processes of Poyang Lake subject to engineering control - Ho, Hinchung; Liang, Dongfang; Huang, Guoxian; Fu, Shasha; Xu, Xinfa (Hydrology Research, 2021)
Poyang Lake, the largest freshwater lake in China, plays a key role in regulating the hydrology, water quality and ecosystem in the middle reaches of the Yangtze River. Recent industrialization and urbanization in Jiangxi province have led to rapid increase in water consumption and water quality deterioration. In this research, a numerical model is developed to simulate the hydrodynamics and water quality evolutions in Poyang Lake and its surrounding river network. The study links an in-house one-dimensional river network model with a MIKE multi-layered three-dimensional hydro-environmental model. The validated model is used to investigate the impact of a proposed downstream barrage on Poyang Lake's flow and ecosystem. All of the five considered barrage operation schemes demonstrate the capability of increasing the water level and inundation area during the dry period, especially in the lake's downstream region. The barrage schemes help reduce the lake's nutrient concentrations, due to the enhanced dilution at higher water levels. Nonetheless, the barrage leads to DO depletion which could pose a threat to the aquatic wildlife and habitats. This study's findings contribute to a better understanding of the hydro-environmental influence of the proposed barrage and thus the optimisation of its operation to mitigate the adverse influence.